Extraction, Physicochemical Properties, and In Vitro Antioxidant Activities of Chondroitin Sulfate from Bovine Nose Cartilage - Chan Shi; Yuxuan Deng; Xin An; Yuan Chen; Xingang Lv; Qian Liu (International Journal of Food Science)
Beef is an important high-nutrition livestock product, and several byproducts, such as bovine cartilage, are produced during slaughter. To effectively utilize these agricultural and pastoral byproducts, combined (trypsin-papain) enzymolysis and cetylpyridine chloride purification methods were used to obtain chondroitin sulfate (CS) from the nasal cartilage of Shaanxi Yellow cattle. The effects of pH, temperature, and time on the CS yield during enzymatic hydrolysis were investigated, and the CS extraction process was optimized using response surface methodology. The best yield of CS was 21.62% under the optimum conditions of pH 6.51, temperature of 64.53°C, and enzymolysis time of 19.86 h. The molecular weight of CS from Shaanxi cattle nasal cartilage was 89.21 kDa, glucuronic acid content was 31.76±0.72%, protein content was 1.12±0.03%, and sulfate group content was 23.34±0.08%. The nasal cartilage CS of the Yellow cattle showed strong DPPH•, •OH, and ABTS+• radical scavenging abilities and ferrous reduction ability in the experimental concentration range. This study could contribute to “turn waste into treasure” and improve the comprehensive utilization of regional characteristic biological resources.